Peningkatan Kapasitas Pemasaran Digital UMKM melalui Pendampingan Pemanfaatan Artificial Intelligence dalam Pembuatan Konten Promosi - Puspita Lianti Putri; Budi Widadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aimed to enhance the digital marketing capacity of MSME actors in Banyumas Regency through assistance in utilizing Artificial Intelligence for promotional content creation. The main problem faced by the partners was their limited ability to consistently prepare captions, product descriptions, content ideas, and posting calendars, although most of them had already used digital media such as WhatsApp Business, Instagram, TikTok, marketplaces, and Google Business Profile. This activity was carried out using a participatory-educational approach through several stages, namely preparation, training, hands-on practice, mentoring, and evaluation. The participants consisted of 25 MSME actors from the culinary, fashion, handicraft, service, processed product, and trading sectors. The media used in this activity included training modules, AI prompt templates, product identity worksheets, content calendar templates, and a WhatsApp mentoring group. The results showed an improvement in participants’ understanding, as indicated by an increase in the average pre-test score from 51.4 to 84.0 in the post-test. All participants were able to create promotional captions, product descriptions, and content ideas with the assistance of AI. Furthermore, 88 percent of participants were able to develop a weekly content calendar, and 92 percent produced ready-to-upload promotional content. Follow-up mentoring also showed that some participants had begun publishing content on digital media and receiving customer responses. This activity demonstrates that the utilization of Artificial Intelligence can serve as a practical, simple, and applicable solution to help MSMEs improve the quality of their digital promotional content.